2018
DOI: 10.3390/ijerph15091798
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Metabolic Syndrome Prevalence by Employment Type and Sex

Abstract: Workers may sometimes do the same work, but differ in their risk of health-related problems depending on whether the employment type is standard or non-standard. Furthermore, even with similar job and employment types, there may be differences in risk factors for health-related problems depending on sex. This study aimed to determine the prevalence of metabolic syndrome (MetS) by employment type and sex using data from the Fifth Korean National Health and Nutrition Examination Survey (KNHANES Ⅴ) (2010–2012) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
1
20
1
2
Order By: Relevance
“…With respect to gender difference, in our study, multivariate analysis identified sex (male) [2.337 (2.012, 2.714), p < 0.001]) as one of independent risk factors for MetS. This result may be conflicted with some previous studies [36][37][38] . However, it was consistent with several European studies which had indicated lower prevalence in women than in men [39][40][41][42] .…”
Section: Discussioncontrasting
confidence: 83%
“…With respect to gender difference, in our study, multivariate analysis identified sex (male) [2.337 (2.012, 2.714), p < 0.001]) as one of independent risk factors for MetS. This result may be conflicted with some previous studies [36][37][38] . However, it was consistent with several European studies which had indicated lower prevalence in women than in men [39][40][41][42] .…”
Section: Discussioncontrasting
confidence: 83%
“…In Marquezine et al study 15 , general prevalence of MetS was not significantly different between genders, but a clear relation was established between the prevalence and progressing of age. In another study, the prevalence of MetS significantly increased with age only among male participants 16 , while in other study it increased in both men and women 17 . www.nature.com/scientificreports/ In our study, employment and education level as an indication of social status was linked to the MetS in the univariable analysis, and similar results were reported in some other studies.…”
Section: Demographic and Social Risk Factors Related To Metabolic Synmentioning
confidence: 74%
“…Part-time or temporary workers of either gender showed higher MetS prevalence than full-time workers 16 , but job rank was not associated with MetS in Mehrdad et al study 18 . The prevalence of MetS significantly augmented with being married 16 , and smoking status 16,19 . The odds ratios (ORs) of suffering from MetS was significantly higher amongst people who smoked at least 20 cigarettes/day 20 .…”
Section: Demographic and Social Risk Factors Related To Metabolic Synmentioning
confidence: 75%
See 1 more Smart Citation
“…There has been interest in assessing the prevalence of this syndrome among industry workers, and several studies have presented estimates for countries such as India, Korea and Japan. [2][3][4] Other studies have investigated the relationship of MetS with sex and industry sector. However, the relationship of MetS with food and nutrition public policy programs has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%